Characteristics of the 19th Century French Opera reflected in the Works of Saint-Saëns and Bizet - Karácsony, Noémi (Babes-Bolyai University Cluj-Napoca, 2018)
The present paper aims to reveal the essential features of 19th century French opera, highlighting those aspects which contributed to the eventual crystallization of a dramatic work seeking to reflect the characteristics of French music and culture. The manner in which melody, harmony, rhythm, dynamics, tempo and timbres are used is analysed, focusing on two representative works of the French Romanticism: Saint-Saëns’ Samson et Dalila and Bizet’s Carmen. Harmonic innovations, floating melodies, strong rhythmic patterns along with the marked influence of folklore and Oriental culture contribute to the distinguishing of 19th century French opera. Finally, attributes of the French singing school and the role of the mezzo-soprano voice in the compositions of the 19th century French operas are revealed.
Keywords: opera; French; Saint-Saëns; Bizet; mezzo-soprano.